Warren Buffett Accounting Book: Reading Financial Statements for Value Investing - Stig Brodersen; Preston Pysh (USA Pylon Publishing, 2014)
This book is the second volume to the Amazon Bestseller Warren Buffett's Three Favorite Books. In this book, you will learn how to: Pick stocks like Warren Buffett Calculate the intrinsic value of stocks using two methods During the second half of the book, readers will learn in-depth methods for: Read an income statement Read a balance sheet Read a cash flow statement Calculate and interpret key ratios
Keywords: Business; Investments; Personal Finance; Finance; Nonfiction; Economics